Representações sociais do conteúdo da Revista Cocar sobre formação de professores e relações étnico-raciais (2010 a 2021) - SILVA, Ila Naiara Castro da (2022)
This study analyzes the Social Representations of the Content of the Cocar Journal on Teacher Education and Ethnic-Racial Relations (2010 to 202). It discusses that social representations about Teacher Education and Ethnic-Racial Relations are contained in the productions of this scientific journal. The research is based on the Theory of Social Representations (TSR), supported by Serge Moscovici. The theoretical framework in the field of Teacher Education is based on Bernadete Gatti, Selma Garrido Pimenta, José Contreras, Leonor Tanuri and Maurice Tardif. For the incursion on Ethnic-Racial Relations, we have referenced Antonio Sant'Ana, Nilma Gomes, Raquel Amorim dos Santos, Silvio Almeida, among others. The research is qualitative, bibliographic, conducted through a bibliographic survey of articles in the Cocar Journal (PPGED / UEPA), in the period from 2010 to 2021. Methodologically, the Tridimensionality (information, image and attitude) of Serge Moscovici was used, aiming to capture the anchoring and objectification processes, essential in the formation of representations, because from these foundations it is possible to create and give meaning to reality. The data generation was done through a bibliographic survey of articles from this scientific journal, considering as a selection criterion the use of the theme in the field of knowledge of Teacher Education and Ethnic-Racial Relations. We used the speech analysis from the discursive dialogism of Mikhail Bakhtin. The results reveal that the social representations emerging from the articles in the Cocar Journal present theoretical and methodological contributions that promote the confrontation of racism in the field of education. Nevertheless, it was evident that the amount of research on the theme Teacher Education and Ethnic-Racial Relations in the productions of Cocar Journal was very limited. This is a result of the invisibility of Afro-Brazilian and African history and culture in the context of educational institutions and its unfolding in scientific productions. In conclusion, it is necessary to expand the theme of Teacher Education and Ethnic-Racial Relations in Cocar Journal. The insertion of this field of study in the productions of scientific journals contributes to the breaking down of racist stereotypes and the expansion and dissemination of scientific research in the field of Teacher Training and Ethnic-Racial Relations aiming at the recognition and appreciation of studies on Afro-Brazilian and African history and culture.